Hangman's root A China Bayles Mystery - Albert, Susan Wittig (New York : Scribner's, 1994)
In Texas, a biologist who experimented on animals is found hanged in his office and suspicion focuses on Dottie Riddle, an animal rights activists. At that China Bayles, her friend, a woman who gave up law to run a herb shop, realizes she has to return to her old trade.
Keywords: Bayles, China (Fictitious character); Women detectives -- Texas; Herbalists; Texas; Mystery fiction